MiR-142-5p in Bone Marrow-Derived Mesenchymal Stem Cells Promotes Osteoporosis Involving Targeting Adhesion Molecule VCAM-1 and Inhibiting Cell Migration. (29th March 2018) - Teng, Zhaowei; Xie, Xueguan; Zhu, Yun; Liu, Jianping; Hu, Xingbo; Na, Qiang; Zhang, Xiongwen; Wei, Guojun; Xu, Shen; Liu, Yugang; Zhang, Xiguang; Xian, Cory J.
Abstract : Osteoporosis is a systemic bone metabolic disease that is highly prevalent in the elderly population, particularly in postmenopausal women, which results in enhanced bone fragility and an increased susceptibility to fractures. However, the underlying molecular pathogenesis mechanisms still remain to be further elucidated. In this study, in a rat ovariectomy- (OVX-) induced postmenopausal osteoporosis model, aberrant expression of a microRNA miR-142-5p and vascular cell adhesion molecule 1 (VCAM-1) was found by RNA sequencing analysis and qRT-PCR. Using a dual-luciferase reporter assay, we found that miR-142-5p can bind to and decrease expression of VCAM-1 mRNA. Such reduction was prohibited when the miR-142-5p binding site in VCAM-1 3′UTR was deleted, and Western blotting analyses validated the fact that miR-142-5p inhibited the expression of VCAM-1 protein. Bone marrow-derived mesenchymal stem cells (BMMSCs) transfected with miR-142-5p showed a significantly decreased migration ability in a Transwell migration assay. Collectively, these data indicated the important role of miR-142-5p in osteoporosis development involving targeting VCAM-1 and inhibiting BMMSC migration.